Biotic acts of antibiotics - Aminov, Rustam I. (Frontiers in Microbiology, 2013)
Biological functions of antibiotics are not limited to killing. The most likely function of antibiotics in natural microbial ecosystems is signaling. Does this signaling function of antibiotics also extend to the eukaryotic – in particular mammalian – cells? In this review, the host modulating properties of three classes of antibiotics (macrolides, tetracyclines, and β-lactams) will be briefly discussed. Antibiotics can be effective in treatment of a broad spectrum of diseases and pathological conditions other than those of infectious etiology and, in this capacity, may find widespread applications beyond the intended antimicrobial use. This use, however, should not compromise the primary function antibiotics are used for. The biological background for this inter-kingdom signaling is also discussed.